Solanum betaceum (Tamarillo): A Potential Antioxidant Rich Indigenous Fruit of India - Suganya Arivazhagan; Chinnappan A Kalpana (Amerta Nutrition)
Background: Solanum betaceum, commonly known as tamarillo, a nutritious fruit rich in vitamin C, dietary fibre, and an essential antioxidant that protects cells from free radical damage, contributing to overall health.